Technical Considerations for Development of Policy and Approvals for In-Water Cleaning of Ship Biofouling - Tamburri, Mario N.; Georgiades, Eugene T.; Scianni, Christopher; First, Matthew R.; Ruiz, Gregory M.; Junemann, Carolyn E. (Frontiers in Marine Science, 2021)
Submerged ship surfaces are often inhabited by diverse sessile and sedentary marine organisms, which can directly impact vessel operations and increase the likelihood of non-indigenous species (NIS) establishment and impacts. Ship in-water cleaning (IWC) systems are now being incorporated into biofouling policy, and rigorous, transparent, and predictive verification testing is vital to regulatory success. Performance criteria for IWC approval should focus on environmental protection goals by including: qualified and independent testing; quantitative, robust, and statistically sound data, rather than qualitative observations; water sampling at all critical control points to characterize the release of harmful materials, including dissolved and particulate biocides; measurable and protective endpoints, rather than percent reductions; determinations of presence or absence of macro-organisms, irrespective of species origins or physiological state; and appropriately trained IWC operators.